The traditional Chinese medicine manipulation combined with Schroth exercises for adolescent idiopathic scoliosis: protocol for a randomized controlled trial - Tao, Jun; Li, Hongjian; Zhang, Guilong; Hu, Rong; Liao, Tangyu; Wang, Fei; Yin, Zi; Feng, Wenqi (Frontiers in Pediatrics, 2025)
IntroductionAdolescent idiopathic scoliosis (AIS) is a three-dimensional spinal deformity that can impair posture, function, and quality of life. Schroth exercise, a physiotherapeutic scoliosis-specific exercise, has demonstrated benefits in reducing Cobb angle and improving patient-reported outcomes. Traditional Chinese Medicine (TCM) manipulation may modulate musculoskeletal asymmetry and pain, potentially exerting synergistic effects when combined with Schroth therapy. This study aims to evaluate whether TCM manipulation plus Schroth exercise is superior to Schroth exercise alone in improving spinal curvature, patient-centered outcomes, and paraspinal symmetry in AIS.MethodsThis is a single-center, randomized controlled, two-arm parallel-group superiority trial. Sixty adolescents (aged 10–18) with idiopathic scoliosis and Cobb angle 10°–45° will be randomized 1:1 to: (1) Schroth therapy alone (control) or (2) TCM manipulation combined with Schroth exercise (intervention). Primary outcome is change in Cobb angle measured by full-length standing anteroposterior spinal radiograph before and after the intervention. Secondary outcomes include Angle of Trunk Rotation (ATR), paraspinal thermal asymmetry assessed by infrared thermography, and health-related quality of life measured by the Scoliosis Research Society-22r (SRS-22r) questionnaire. Participants will be randomly allocated (1:1) using a computer-generated, stratified block randomization sequence with allocation concealed by sealed opaque envelopes. The analysis will follow the intention-to-treat (ITT) principle, and an ANCOVA adjusting for baseline measurements will be used for between-group comparisons. A total sample size of 60 participants (30 per group) was determined a priori to provide 80% power (α = 0.05, β = 0.20) to detect a clinically meaningful difference in Cobb angle, allowing for a 20% attrition rate.DiscussionIf effective, the combined regimen could offer a non-invasive, integrative therapeutic option for AIS, with implications for conservative management guidelines.Ethics and disseminationThe study protocol was approved by the Ethics Committee of Yibin Traditional Chinese Medicine Hospital [Approval No. KY2024 Review (016)]. The trial has been prospectively registered in the International Traditional Medicine Clinical Trial Registry (ITMCTR) on January 6, 2025. The study will be conducted in accordance with the principles of the Declaration of Helsinki (Edinburgh 2000 revision). The trial findings will be disseminated through publication in peer-reviewed journals.Trial registrationThe full trial protocol and statistical analysis plan can be accessed via the ITMCTR website (Registration No. ITMCTR2025000131). Any important modifications to the protocol will be submitted for approval by the institutional ethics committee and updated in the ITMCTR.